A new method of removing atmospheric effects using Pseudo-invariant targets - Hadjimitsis, Diofantos G.; Clayton, C.R.I.; Hope, V. S.; Retalis, Adrianos (My University, 1999)
A new method of removing atmospheric effects using pseudo-invariant targets - ePrints Soton The University of Southampton Courses University life Research Business Global About Visit Alumni Departments News Events Contact × Search the Site Search Filter your search: All Courses Projects Staff University of Southampton Institutional Repository Search Advanced Search Policies & Help Latest Download Statistics Browse by Year Browse by Divisions LeftRight A new method of removing atmospheric effects using pseudo-invariant targets Hadjimitsis, DG, Clayton, CRI, Hope, VS and Retalis, A. (1999) A new method of removing atmospheric effects using pseudo-invariant targets. 25th Annual Conference and Exhibition of the Remote Sensing Society: Earth Observations - From Data to Information, Swansea, United Kingdom. Record type: Conference or Workshop Item (Paper) This record has no associated files …
Keywords: TM Images; Pseudo-invariant Targets; Atmospheric correction methodology